Establishing a common metric for self‐reported anxiety in patients with prostate cancer: Linking the Memorial Anxiety Scale for Prostate Cancer with PROMIS Anxiety. Issue 18 (15th May 2019) - Victorson, David; Schalet, Benjamin D.; Kundu, Shilajit; Helfand, Brian T.; Novakovic, Kristian; Penedo, Frank; Cella, David
Abstract : Background: Anxiety is a common patient concern and clinical endpoint in prostate cancer outcomes research. It is measured using different self‐report instruments that are not directly comparable, thereby making clinical trials, clinical performance measurement, and comparative effectiveness research challenging when anxiety is the outcome of interest. The objective of the current study was to enable a common reporting metric of anxiety so that scores on commonly used anxiety measures could be converted into Patient‐Reported Outcomes Measurement Information System (PROMIS) scores for ease of application, interpretation, and comparability. Methods: Using an internet health panel, a total of 806 men with clinically localized prostate cancer completed items from the National Institutes of Health PROMIS Anxiety Short Form (version 7a) and the 18‐item Memorial Anxiety Scale for Prostate Cancer (MAX‐PC). A common metric was created using analyses based on item response theory, producing score crosswalk tables. The linking relationships were evaluated by resampling small subsets and estimating confidence intervals for the differences between the observed and linked PROMIS scores. Results: Results of factor analysis and item response theory model fit supported the hypothesis that both scales measure essentially the same concept. Therefore, crosswalk tables appear to be justified and increasingly robust with increasing sample sizes. Conclusions: MAX‐PC Anxiety results can be expressed on the PROMIS Anxiety metric for the purposes of clinical performance measurement, clinical trial outcomes, comparative effectiveness research, and other efforts to compare anxiety results across studies that use any one of these measures. Abstract : To date, it has not been possible to compare scores from different anxiety measures administered in different prostate cancer research studies. The results of the current study indicate that Memorial Anxiety Scale for Prostate Cancer (MAX‐PC) Anxiety results can be expressed on the Patient‐Reported Outcomes Measurement Information System (PROMIS) Anxiety score metric for the purposes of comparative effectiveness research.